Uji Iritasi Kulit Sediaan Sunscreen Spray yang Mengandung Ekstrak Bunga Telang (Clitoria ternatea) dengan Metode Patch Test - Nyoman Rudi Kusuma; Nanik Sulistyani; Nining Sugihartini (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Butterfly pea flower (Clitoria ternatea) contains high levels of anthocyanins with potent antioxidant activity, making it a promising natural ingredient for sunscreen formulations. However, the skin safety of sunscreen spray containing this extract must be evaluated before cosmetic application. Objective: This study aimed to evaluate the skin irritation potential of sunscreen spray formulations containing butterfly pea flower extract using the patch test method. Methods: A patch test was conducted on 15 male Wistar rats. The test materials included sunscreen spray formulations with butterfly pea flower extract at concentrations of 1% (F1), 2% (F2), and 3% (F3). A base formulation without extract (F0) served as a negative control, and sodium lauryl sulfate served as a positive control. Erythema and edema scores were observed at 24, 48, and 72 hours after application. Results: The mean erythema and edema scores for formulations F1, F2, and F3 were 0.0 ± 0, indicating no signs of skin irritation in all tested groups. The positive control group showed slight erythema (score 2.33 ± 0.5), confirming the validity of the test method. Conclusion: Sunscreen spray formulations containing butterfly pea flower extract at concentrations of 1%, 2%, and 3% did not induce skin irritation in male Wistar rats under the patch test conditions. These findings support the potential of butterfly pea flower extract as a safe natural ingredient for sunscreen products.